Mechanisms underlying epigenetic and transcriptional heterogeneity in Chinese hamster ovary (CHO) cell lines. Issue 1 (December 2016) - Veith, Nathalie; Ziehr, Holger; MacLeod, Roderick; Reamon-Buettner, Stella
Abstract Background Recombinant cell lines developed for therapeutic antibody production often suffer instability or lose recombinant protein expression during long-term culture. Heterogeneous gene expression among cell line subclones may result from epigenetic modifications of DNA or histones, the protein component of chromatin. We thus investigated in such cell lines, DNA methylation and the chromatin environment along the human eukaryotic translation elongation factor 1 alpha 1 (EEF1A1 ) promoter in an antibody protein-expression vector which was integrated into the Chinese hamster ovary (CHO) cell line genome. Results We analyzed four PT1-CHO cell lines which exhibited losses of protein expression at advanced passage number (>P35) growing in adherent conditions and in culture medium with 10 % FCS. These cell lines exhibited different integration sites and transgene copy numbers as determined by fluorescence in situ hybridization (FISH) and quantitative PCR (qPCR), respectively. By qRT-PCR, we analyzed the recombinant mRNA expression and correlated it with DNA methylation and with results from various approaches interrogating the chromatin landscape along theEEF1A1 promoter region. Each PT1-CHO cell line displayed specific epigenetic signatures or chromatin marks correlating with recombinant mRNA expression. The cell line with the lowest recombinant mRNA expression (PT1-1) was characterized by the highest nucleosome occupancy and displayed the lowest enrichment for histone marks associated with active transcription. In contrast, the cell line with the highest recombinant mRNA expression (PT1-55) exhibited the highest numbers of formaldehyde-assisted isolation of regulatory elements (FAIRE)-enriched regions, and was marked by enrichment for histone modifications H3K9ac and H3K9me3. Another cell line with the second highest recombinant mRNA transcription and the most stable protein expression (PT1-7) had the highest enrichments of the histone variants H3.3 and H2A.Z, and the histone modification H3K9ac. A further cell line (PT1-30) scored the highest enrichments for the bivalent marks H3K4me3 and H3K27me3. Finally, DNA methylation made a contribution, but only in the culture medium with reduced FCS or in a different expression vector. Conclusions Our results suggest that the chromatin state along theEEF1A1 promoter region can help predict recombinant mRNA expression, and thus may assist in selecting desirable clones during cell line development for protein production.